The Use of Connectors in the Writing of Libyan EFL Students: A study in the English Department, Sirte University (Journal of Academic Research, 2019)
This study explores the sorts of problems Libyan Learners of English as a Foreign Language (LLsEFL henceforth) have in using connectors. Composition essays written by participants of this study were used to measure the proper and the improper use of connectors. The essays were then analysed quantitatively and qualitatively. Findings revealed that the problems LLsEFL experience in using connectors can be classified into three categories: misuse, underuse and overuse. Results indicated also that misuse was the most common problem followed by underuse and overuse respectively. In addition, they showed that adversatives were the most commonly misused category whereas additives were the most overused and temporals were the most underused. The qualitative analyses suggested that the cause for the majority of misuse of connectors was generally attributed to semantic, stylistic and discoursal problems. The underuse and overuse were mainly attributed to first language interference.